Clarks brings digital touch to traditional shoemaking - Authers, Ross (Knovel, 2012)
Thanks to 3D CAD software and 3D printers, Clarks has moved from hand-drawn sketches and factory-manufactured samples to creating prototypes in a digital world, decreasing costs and improving its time-to-market agility.
Knovel brief article.
Keywords: C. & J. Clark Ltd.; Shoemakers.; Computer-aided design -- Computer programs.; Three-dimensional printing.; Production engineering.; elektronické knihy; electronic books